A mixed cumulative sum homogeneously weighted moving average control chart for monitoring process mean. (23rd December 2020) - Abid, Muhammad; Mei, Sun; Nazir, Hafiz Zafar; Riaz, Muhammad; Hussain, Shahid; Abbas, Zameer
Abstract: The homogeneously weighted moving average (HWMA) control chart is famous to identify small deviations in the process mean. The plotting statistic of the HWMA chart assigns equal weight among the previous samples as compared to the plotting statistic of the exponentially weighted moving average chart. We propose a new HWMA chart that uses the plotting statistic of the cumulative sum chart. The run length performance of the proposed chart is measured in terms of the average, the standard deviation, some percentile points, and compared with some existing counterparts' charts. The comparison shows that the proposed chart performs superior to their existing counterparts. An application based on a real‐life dataset is also presented.